The impact of degree class on the first destinations of graduates: A regression discontinuity approach - Giorgio Di Pietro (Institute for the Study of Labor (IZA), 2010)
This paper uses a regression-discontinuity design to identify the causal impact of degree class on the first destinations of UK graduates. We exploit the discontinuous relationship between degree class and the mean grade achieved by graduates in their last year at university, which is induced by the administrative rules used for the determination of degree class. More specifically, we compare the average first-destination outcome of graduates with a mean grade that just allowed them to get a given class of degree with the average first-destination outcome of those with a mean grade that made them just miss the chance of achieving the same class of degree. Our empirical analysis focuses on graduates who graduated from a post-1992 university in the period January-July 2008. The results are consistent with the view that degree class does not truly affect the first destinations of graduates, but it picks up the effect of other ability indicators that are typically not observed by researchers. Hence this finding questions the signaling role of degree class.
Keywords: I21; J24; J23; 330; First destinations of graduates; regression discontinuity design; degree classification; Berufseinstieg; Akademische Berufe; Bildungsabschluss; Schätzung; Großbritannien